PELAKSANAAN INFORMED CONSENT DALAM TRANSAKSI TERAPEUTIK PADA TINDAKAN BEDAH DI RUMAH SAKIT BHAYANGKARA PEKANBARU PROVINSI RIAU - Tio Pujakusuma; Maryati Bachtiar; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Informed consent is a standard medical service that must be available before conducting medical treatment, because with this opportunity the parties have bound themselves so that rights and obligations arise, and on the other hand also serves as a basis for prosecuting if medical action occurs outside what has been agreed or promised. The consequences of actions that do not comply with informed consent can be the occurrence of errors or negligence. One hospital that provides health services in the city of Pekanbaru is the Bhayangkara Regional Police Hospital which in carrying out its health services also entered into a health service agreement. But based on existing data that , Many problems and obstacles arise in medical practice everyday, such as comprehension and language information delivery that are less obvious, limit the amount of information that touched s / can be given, and the problem of interference of a family or a third party in terms of giving consent in Hospital Bayhangkara City Pekanbaru and compared with standart operating procedur and applicable law. destination this thesis, namely: First to determine pime Frame informed consent to the transaction therapeutic surgery at the Bhayangkara Hospital in Pekanbaru, Riau Province, Second, to determine the responsibility of medical services to patients based on the approval of medical measures at the Bhayangkara Hospital Pekanbaru.This type of research can be classified as sociological. This study was conducted at Hospital Bayhangkara Pekanbaru city, while the population and until l was a whole party with regard to the issues examined in this study, the source of the data used primary data , the data secondary data and ter s IER, data collection techniques in this study with interviews , questionnaires and literature review.From the results of the study it can be concluded two things. First, the process of implementation of informed consent in the House for pain Bayhangkara city of Pekanbaru, health workers must first provide full information to the patient about the results of observation, diagnosis and action will be taken physician and patient may give consent after the receipt of such information and determine implemented or not action medical on him. because of the low understanding of the community, especially consumers / surgical patients of informed consent prior to taking action at Bhayangkara Hospital. Second, business actors' obligations as health providers have not been fulfilled, namely explaining or providing understanding of informed consent to surgical patients at Bhayangkara Hospital. Implementation of the understanding of informed consent in the approval of medical treatment at the Bhayangkara Pekanbaru Hospital is an important matter but has not been carried out as it should, as in the completeness of filling out the approval of medical measures so that there is no clear responsibility for health services to surgical patients. The first government through the minister of health should reinforce the rules for health services through health workers not to commit acts of medicine according to the procedure that is right in the neighborhood Police Hospitals, secondly, each health worker should be able to undestand rights and responsibilities in accordance with the Laws Regulations and Regulations that apply in the Bhayangkara Hospital environment.Keywords: Informed Consent - Hospital - Transactio